Meta-analysis of crop responses to conservation agriculture in sub-Saharan Africa - Corbeels, Marc; Sakyi, RK; Kühne, Ronald F.; Whitbread, Anthony M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2014)
Conservation agriculture involves reduced or no-tillage, permanent soil cover and crop rotations to enhance soil fertility and crop yields. Conservation agriculture practices are increasingly promoted on smallholder farms in sub-Saharan Africa as a means to overcome continuing poor-profitability and soil degradation. In recent years a growing number of studies have been carried out in sub-Saharan Africa comparing conservation agriculture practices to conventional tillage-based practices. These studies have been conducted under a range of conditions (climate, soil, management, cropping system) gaining variable results on crop yield responses. The aim of this study is to compare and combine the results from different conservation agriculture experiments using meta-analysis in the hope of identifying patterns among study results, sources of disagreement among those results, or interesting relationships that may come to light in the context of the different studies.